2022
DOI: 10.36989/didaktik.v7i02.220
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Pembelajaran Berbasis Hots (High Order Thinking Skill) Di Sekolah Dasar Kota Malang

Abstract: HOTS (High Order Thinking Skill) is material used by the students for helping the achievement of the competency standard , the purpose of education of primary and competence have (Depdiknas.2006) This study aims to describe the implementation of learning based on High Order Thinking Skills (HOTS) in Elementary Schools in Malang. It is well known that the implementation of the 2013 curriculum suggests that the importance of applying HOTS to the learning process in elementary schools. Therefore, it is necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to Budiarta et al, (2018) stated that HOTS is meaningful as a complex thinking process consisting of the ability to describe material, criticize, and create alternative solutions to a problem. Meanwhile, Annuuru et al, (2017) revealed that HOTS is the ability in the process of analyzing, evaluating, and creating through a process of combining phenomena and an idea in the form of an evaluation of the facts that have been studied.…”
Section: Analysis Of Students' Error In Working On Mathematics Proble...mentioning
confidence: 99%
“…According to Budiarta et al, (2018) stated that HOTS is meaningful as a complex thinking process consisting of the ability to describe material, criticize, and create alternative solutions to a problem. Meanwhile, Annuuru et al, (2017) revealed that HOTS is the ability in the process of analyzing, evaluating, and creating through a process of combining phenomena and an idea in the form of an evaluation of the facts that have been studied.…”
Section: Analysis Of Students' Error In Working On Mathematics Proble...mentioning
confidence: 99%